Parents' Perception of the Development of Cognitive Aspects of Children Aged 5-6 Years in the Context of Activity-Based Stimulation at Home - Stefania Mogi; Andi Nafsia; Konstantinus Dua Dhiu; Efrida Ita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe parents' perception of the development of cognitive aspects of children aged 5–6 years and to describe the forms of activity-based stimulation applied in the home environment. This research method uses a descriptive qualitative approach, with the research subjects of parents who have children aged 5–6 years in Beiposo State Kindergarten. Data collection was carried out through in-depth interviews and documentation, then analyzed using thematic analysis techniques to find patterns of perception and stimulation practices carried out by parents. The results of the study show that in general, parents have a positive view of children's cognitive development. Children have shown the ability to recognize letters and numbers, follow simple directions, and show good curiosity, despite differences in developmental levels between children. The forms of stimulation provided by parents include educational play activities, literacy and numeracy activities, and children's involvement in daily activities. However, the implementation of the stimulation has not been fully carried out consistently because it is influenced by limited time and the level of understanding of parents.